REHABILITATED SOLAR POWER CONSUMED UTILITARIAN CHARGING DEVICE FOR MOBILE PHONE USING ABD - Dr. A. Sundar Raj; B.Prabhavathy; S. Jim Hawkinson (International Journal of Psychosocial Rehabilitation, 2020)
A reformed model on Solar power consumed mobile phone charging by using ABD is proposed in this Paper. Here, solar energy is used for mobile phone charging. It is placed for mobile back cover. Solar energy is converted into electrical energy in order to charge mobile phones. This charging circuit is inbuilt with the mobile case. Whenever the mobile get exposed to sunlight the light energy is converted into electrical energy and get stored in the external battery further it will used for charging when we on the switch. Solar chargers are simple, portable, flexible, high power and never breakable one. Mobile phone has becomes unavoidable in our day to day life, so it can be used for everyone. This will be a socket free handy charging device. The block diagram, circuit diagram, hardware design are discussed in this paper.